2008
DOI: 10.1203/pdr.0b013e31817995aa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Constipation on Growth in Children

Abstract: ABSTRACT:The observation on the impact of constipation on nutritional and growth status in healthy children was never reported. During a 4-y period, we evaluated the consequence of constipation on growth in children. The enrolled children were aged between 1 and 15 y with constipation. Medical response of constipation to treatment was evaluated by the scoring of constipation symptoms. The correlation of therapeutic effect of constipation with growth status at 12 wk and 24 wk was statistically evaluated. About … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
(8 reference statements)
1
23
0
2
Order By: Relevance
“…The obesity was observed in 44 out of 101 constipated children (43.6%) and 30 out of 100 normal control (30%), that are comparable with our findings, although our patients were younger than those analyzed in Misra et al study (6). On the other hand, in another study, Chao et al (4) investigated the growth status of Taiwanese children with constipation, and further evaluated the impact of constipation on growth status during a 12-week and 24-week medical therapy. They reported that near 5% of patients were over weighted (> 90 %) or In obese status, whereas near 25% of patients were underweighted (< 10%) or malnourished.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The obesity was observed in 44 out of 101 constipated children (43.6%) and 30 out of 100 normal control (30%), that are comparable with our findings, although our patients were younger than those analyzed in Misra et al study (6). On the other hand, in another study, Chao et al (4) investigated the growth status of Taiwanese children with constipation, and further evaluated the impact of constipation on growth status during a 12-week and 24-week medical therapy. They reported that near 5% of patients were over weighted (> 90 %) or In obese status, whereas near 25% of patients were underweighted (< 10%) or malnourished.…”
Section: Discussionsupporting
confidence: 91%
“…There are a few data with controversy on the growth status of children with chronic constipation. Chao et al (4) reported the impact of chronic constipation on nutritional and growth status in children. They concluded that chronic constipation may negatively affect the children growth, but after long-term treatments due to the significant increase of appetite, restoration of normal growth was obtained and significant increase of Z-scores of height, weight, and body mass index (BMI) were observed (4).…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model, inducing constipation led to oxidative stress, whereas prebiotics attenuated both constipation and oxidative stress (42). Prolonged duration of constipation in children was found to lead to oxidative stress (43) and growth retardation (44), whereas effective management of constipation attenuated the growth retardation (44). Consequently, assuring proper bowel movement frequency may significantly affect public health.…”
Section: Bowel Movement Frequency Oxidative Stress and Disease Prevementioning
confidence: 99%
“…In addition to colonic distension, abdominal discomfort, gas formation and painful defaecation, chronic constipation may also have deleterious effects on the growth, development and general well being of children. (2) With regard to the latter the psychosocial consequences of constipation are many. Children with constipation will inevitably encounter the embarrassing experience of recurrent episodes of faecal incontinence due to the overflow caused by faecal impaction.…”
Section: Press Releasementioning
confidence: 99%